Safety of natural anthraquinone emodin: an assessment in mice - Alexander T. Sougiannis; Reilly T. Enos; Brandon N. VanderVeen; Kandy T. Velazquez; Brittany Kelly; Sierra McDonald; William Cotham; Ioulia Chatzistamou; Mitzi Nagarkatti; Daping Fan; E. Angela Murphy (BMC, 2021)
Abstract Background Emodin, a natural anthraquinone, has shown potential as an effective therapeutic agent in the treatment of many diseases including cancer. However, its clinical development is hindered by uncertainties surrounding its potential toxicity. The primary purpose of this study was to uncover any potential toxic properties of emodin in mice at doses that have been shown to have efficacy in our cancer studies. In addition, we sought to assess the time course of emodin clearance when administered both intraperitoneally (I.P.) and orally (P.O.) in order to begin to establish effective dosing intervals. Methods We performed a subchronic (12 week) toxicity study using 3 different doses of emodin (~ 20 mg/kg, 40 mg/kg, and 80 mg/kg) infused into the AIN-76A diet of male and female C57BL/6 mice (n = 5/group/sex). Body weight and composition were assessed following the 12-week feeding regime. Tissues were harvested and assessed for gross pathological changes and blood was collected for a complete blood count and evaluation of alanine transaminase (ALT), aspartate transaminase (AST) and creatinine. For the pharmacokinetic study, emodin was delivered intraperitoneally I.P. or P.O. at 20 mg/kg or 40 mg/kg doses to male and female mice (n = 4/group/sex/time-point) and circulating levels of emodin were determined at 1, 4 and 12 h following administration via liquid chromatography with tandem mass spectrometry (LC-MS/MS) analysis. Results We found that 12 weeks of low (20 mg/kg), medium (40 mg/kg), or high (80 mg/kg) emodin feeding did not cause pathophysiological perturbations in major organs. We also found that glucuronidated emodin peaks at 1 h for both I.P. and P.O. administered emodin and is eliminated by 12 h. Interestingly, female mice appear to metabolize emodin at a faster rate than male mice as evidenced by greater levels of glucuronidated emodin at the 1 h time-point (40 mg/kg for both I.P. and P.O. and 20 mg/kg I.P.) and the 4-h time-point (20 mg/kg I.P.). Conclusions In summary, our studies establish that 1) emodin is safe for use in both male and female mice when given at 20, 40, and 80 mg/kg doses for 12 weeks and 2) sex differences should be considered when establishing dosing intervals for emodin treatment.